Kajian Yuridis Tindak Pidana Gratifikasi Oleh Pejabat Negara - Bustomi Bustomi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Corruption is a special criminal act that is regulated outside the Criminal Code (KUHP). Especially because this issue is regulated separately outside the Criminal Code (Criminal Code). Because in accordance with Article 103 of the Criminal Code, it is emphasized that: "The provisions in Chapters II to Chapter VIII of this book also apply to acts which by other statutory provisions are threatened with criminal penalties, unless otherwise provided by law." The criminal act of corruption is categorized as an extraordinary crime that requires extraordinary measures, therefore the participation of various components from both the government and society is very necessary. The conventional methods that have been used have proven to be unable to solve the problem of corruption in society, so handling it must also use extraordinary methods